2022
DOI: 10.1080/07853890.2022.2128399
|View full text |Cite
|
Sign up to set email alerts
|

Early glycaemic variability increases 28-day mortality and prolongs intensive care unit stay in critically ill patients with pneumonia

Abstract: Objective This study aimed to evaluate the effect of early glycaemic variability (GV) on 28-day mortality in critically ill patients with pneumonia. Patients and methods This single-centre retrospective study included patients admitted to the intensive care unit (ICU) due to pneumonia between 2018 and 2019. A total of 282 patients (mean age, 68.6 years) with blood sugar test (BST) results measured more than three times within 48 h after hospitalization and haemoglobin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The improvement of glycemic variability in this patient was also accompanied by other positive impact, including a decrease in insulin dose and a shorter length of stay in the ICU. Study by Kim et al 15 showed that high GV within 48 hours of ICU admission was associated with prolonged ICU stay (>14 days). This patient was successfully transferred from ICU to the medical ward on the 12th day of hospitalization despite high GV (61%) within 24 hours of ICU admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of glycemic variability in this patient was also accompanied by other positive impact, including a decrease in insulin dose and a shorter length of stay in the ICU. Study by Kim et al 15 showed that high GV within 48 hours of ICU admission was associated with prolonged ICU stay (>14 days). This patient was successfully transferred from ICU to the medical ward on the 12th day of hospitalization despite high GV (61%) within 24 hours of ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies have shown that high GV in critically-ill patients is associated with an increased risk of mortality and prolonged ICU stay. [13][14][15] Administration of diabetes specific formula (DSF) has been shown to be associated with significant reductions in postprandial blood glucose, mean blood glucose levels, HbA1C, and mean insulin dose thus contributing to good glycemic variability. 16,17 In the absence of DSF, the use of modified hospital-based enteral formula can be considered.…”
mentioning
confidence: 99%
“…Elevated acute GV has been recognized as a potential predictor of poor survival in patients with sepsis [ 25 ]. High GV has also been associated with adverse outcomes in critically ill patients [ 26 , 27 ], including being an independent risk factor for in-hospital mortality in intensive care unit patients, partly due to an increased risk of ventricular arrhythmias [ 28 ]. Elevated acute GV could be an indicator of unfavorable functional results and death in patients with intracerebral hemorrhage [ 29 ].These results underscore the significance of monitoring and managing GV in various clinical settings to improve patient outcomes and reduce the risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, glycemic variability a measure that carries physiologic and clinical significance. For example, high glycemic variability predicts mortality in populations of critically ill patients and is thought to be the driver of vascular complications of diabetes [ [30] , [31] , [32] , [33] ]. It has also been suggested that measures of glycemic variability may be more reliably diagnostic of impaired glucose tolerance than commonly used clinical measures including the hemoglobin A1c and the oral glucose tolerance test [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%